2022
DOI: 10.1177/10249079211049128
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life and resilience in emergency department healthcare professionals during COVID‐19 in Hong Kong: A cross‐sectional study

Abstract: Background: The professional quality of life of healthcare professionals in emergency departments may be compromised during the COVID-19 pandemic. Objectives: This study aims to examine professional quality of life and resilience as well as their relationships among emergency department healthcare professionals in Hong Kong during the COVID-19 outbreak. Methods: This study employed a cross-sectional design. Healthcare professionals (doctors and nurses) working in emergency departments in Hong Kong were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
4
26
1
1
Order By: Relevance
“…Whilst the effectiveness of the territory-wide vaccination programme is yet to be determined, social distancing remained the first line of prevention and control measures [ 3 ]. Although these measures have shown promise in controlling the spread of COVID-19, they can also induce a wide range of psychosocial impacts on different populations [ 4 7 ]. A systematic review of studies conducted before June 2020 found a high prevalence of symptoms of anxiety (6–51%), depression (15–48%), post-traumatic stress disorder (PTSD) (7–54%), psychological distress (34–38%) and stress (8–82%) amongst the general population in eight countries including China, Spain, Italy, Iran, the United States, Turkey, Nepal and Denmark [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the effectiveness of the territory-wide vaccination programme is yet to be determined, social distancing remained the first line of prevention and control measures [ 3 ]. Although these measures have shown promise in controlling the spread of COVID-19, they can also induce a wide range of psychosocial impacts on different populations [ 4 7 ]. A systematic review of studies conducted before June 2020 found a high prevalence of symptoms of anxiety (6–51%), depression (15–48%), post-traumatic stress disorder (PTSD) (7–54%), psychological distress (34–38%) and stress (8–82%) amongst the general population in eight countries including China, Spain, Italy, Iran, the United States, Turkey, Nepal and Denmark [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huffman, et al, 25 found, in a sample of healthcare workers during the COVID-19 pandemic, that individuals with higher resilience and grit experienced lower stress, anxiety, fatigue, and sleep disturbances. Wong et al, 26 found that higher levels of compassion satisfaction and lower levels of stress and burn-out, were reported by those who experience higher levels of resilience.…”
Section: The Relationship Between Resilience and Fear Of Covid-19 And...mentioning
confidence: 99%
“…Thus, Stamm et al integrated both of them into a broader concept, quality of work life (ProQoL), with compassion satisfaction (CS) which refers to the positive feelings about people’s ability to help others [ 7 , 14 ]. In fact, professional quality of life is about emotions that an individual encounters in his/her job as a helper, it incorporates a combination of positive (compassion satisfaction) and negative aspects (secondary traumatic stress and burnout) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the prevalence of CF, conceptualized in burnout and secondary traumatic stress leads us to explore a critical term “resilience” which is a dynamic process of positive coping despite experiencing traumatic events and exhaustion [ 16 , 17 ]. In fact, it has been recognized as a key protective factor against the effects of CF among HCWs in numerous studies worldwide [ 18 ].…”
Section: Introductionmentioning
confidence: 99%